Upper extremity nerve lesions (diagnosis, indications, surgical techniques) - Abreu, Lauro Barros de (São Paulo Medical Journal, 1997)
OBJECTIVE: Revision and questioning of orthodox principles regarding the conduction of nerve impulse. DESIGN: Retrospective study with clinical analysis of results. SITE: Hospital das Clinicas (HCFMSP), public university institution with research programs and tertiary attention to health. GROUP MEMBERS: Author and a team of residents and trainees. OPERATION: Direct suture of nervous stumps utilizing auxiliary technical procedures:- joint-flexion, nerve transposition, tendon transplants, bone shortening. MEASUREMENT: Clinical evaluation and objective tests for tactile and stereognostic function recovery (WeberTest). RESULTS: Variable, depending on preoperative conditions: - type of lesion, time elapsed since injury. CONCLUSIONS: Neurorrhaphy should be the procedure of choice even for long term lesions, although the expected results may be less favourable. Periodical evaluation from 24 hs. postoperative, checking for early undefined signals of nervous function recovery. Association of specific drugs for chemical biophysics of the nerve.